IMPLEMENTASI KEBIJAKAN PERATURAN MENTERI SOSIAL REPUBLIK INDONESIA NOMOR 29 TAHUN 2012 TENTANG TARUNA SIAGA BENCANA DALAM PENANGGULANGAN BENCANA DI KOTA SEMARANG - Ersad, Fauzan; Hidayat, Zainal (Journal of Public Policy and Management Review, 2016)
The backgroud of this research is has not been going well the implementation of disaster management in the city, it is characterized by not maximal implementation at the time of pre-disaster, emergency management and post-disaster.The purpose of this research is to describe how Implementation of the Minister of Social Affairs of the Republic of Indonesia Regulation number 29 year 2012 on Cadets Disaster Preparedness in Semarang that can be rated through three phenomenons, which is pre-disaster, emergency management, and post-disaster. This research uses descriptive qualitative method. The results of the implementation of the Minister of Social Affairs of the Republic Indonesia Regulation number 29 year 2012 on Cadets Disaster Preparedness in Semarang City. Researchers analyzed the factors that support and hinder found in the field include a lack of compatibility between policy and implementing organizations, community support, communications between the lines, the availability of human resources and the allocation of financial resources. The study recommends among other things that need to increase resources both in quantity and quality, to maximize early warning systems, enhance the activity in the delivery of information to the target audience, and maximize the role in the handling of psychosocial services to victims.